2017
DOI: 10.1186/s12885-017-3471-6
|View full text |Cite
|
Sign up to set email alerts
|

Joint quantitative measurement of hTERT mRNA in both peripheral blood and circulating tumor cells of patients with nasopharyngeal carcinoma and its clinical significance

Abstract: BackgroundThe study was aimed to quantitatively detect mRNA levels of the catalytic subunit of telomerase (hTERT) in both peripheral blood and circulating tumor cells (CTCs) of patients with nasopharyngeal carcinoma (NPC) and explore its significance in early diagnosis and treatment of NPC.MethodshTERT mRNA levels in peripheral blood and CTCs of 33 NPC patients before and after treatment with intensity-modulated radiation therapy (IMRT) or/and chemotherapy and 24 healthy controls were measured using real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…www.oncotarget.com demonstrated in breast cancer [17,37]. Albumin mRNA has also been detected in the peripheral blood of advanced stage (TNM stages III and IV) HCC patients.…”
Section: Oncotarget 2236mentioning
confidence: 97%
See 1 more Smart Citation
“…www.oncotarget.com demonstrated in breast cancer [17,37]. Albumin mRNA has also been detected in the peripheral blood of advanced stage (TNM stages III and IV) HCC patients.…”
Section: Oncotarget 2236mentioning
confidence: 97%
“…Several laboratories have demonstrated the existence of circulating mRNA in healthy subjects and those with a disease diagnosis [3][4][5][6][7][8][9][10][11][12][13]. For example, circulating hTERT mRNA levels have been reported to correlate with a diagnosis of hepatocellular carcinoma (HCC) [14,15] and with tumor progression [12,16,17]. Albumin (ALB) mRNA has also been detected in the circulation of advanced stage HCC patients and was reported to predict recurrence of HCC after transplantation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are often limited by tumor size and location, low compliance rate, and the inability to achieve real-time monitoring. Previous studies have revealed that circulating tumor cells (CTCs) are reliable indicators that may be used for the early prediction of tumor recurrence and metastasis, thereby facilitating clinical intervention, and improving patient survival and quality of life (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Further research is required to understand its clinical applications, including quantitative properties [75]. Although RNA is generally unstable in the blood, miR is a stable noncoding molecule consisting of 18-25 nucleotides [16][17][18][19]. This form of endogenous, single-stranded RNA has been implicated in a range of pathological processes, including cancer initiation and progression, and the remarkable stability makes it a useful biomarker for cancer diagnosis [16][17][18][19].…”
Section: Cell-free Rnamentioning
confidence: 99%
“…Recent studies have shown that in addition to DNA, cfNAs such as messenger RNA (mRNA), microRNA (miR), long noncoding RNA (lncRNA), and circular RNA (cir-cRNA) can be detected in the blood and are thus candidate blood-based biomarkers [16][17][18][19]. Other studies have suggested that some of these cfNAs present in the circulating blood are encapsulated in microvesicles such as exosomes, which ensures their stability.…”
Section: Introductionmentioning
confidence: 99%